Into the backyard: Multiple detections of PCV-2e in rural pig farms of Northern Italy. An unexpected ecological niche? - Giulia Faustini; Claudia Maria Tucciarone; Matteo Legnardi; Laura Grassi; Giacomo Berto; Michele Drigo; Mattia Cecchinato; Giovanni Franzo (Preventive Veterinary Medicine, 2023)

First genetic detection and characterization of canine parvovirus type 2 (Carnivore protoparvovirus 1) in southwestern Ethiopia - Dechassa Tegegne; Girma Tsegaye; Giulia Faustini; Giovanni Franzo (Veterinary Research Communications, 2023)
The species Carnivore protoparvovirus 1 includes viruses, e.g. canine parvovirus (CPV-2) and feline panleukopenia virus (FPV), which are among the most relevant for pets, causing extremely severe clinical signs and high fatality rate in dogs and cats. Moreover, a broad range of wild hosts, including endangered ones, were proven to be susceptible. Currently, no data on CPV-2 molecular epidemiology and strain characterization are available in Ethiopia, also considering the frequent contacts between domestic and wild populations. In the present study, a molecular epidemiology survey was performed on 92 fecal samples collected from domestic ( n = 84) and stray ( n = 8) dogs in southwestern Ethiopia in 2021. Approximately, 10% of the samples tested positive and the complete VP2 sequences of 5 strains were obtained, classified within the CPV-2a ( n = 1) and CPV-2c ( n = 4) antigenic variants. In most instances, the closest genetic relatives were strains of Chinese origin, which is fully compatible with the intense relationships that have been developing between the two countries, involving human being travels and their pets as well. Considering the clinical relevance of this infection and the risk it poses to local domestic and wild carnivore populations, especially endangered ones, much stronger monitoring and surveillance activity on foreign incoming animals should be performed. More strict constraints on animal introduction, e.g. compulsory vaccination, should also be considered.

Investigation of Carnivore protoparvovirus 1 and Amdoparvovirus infections in red fox populations of the Italian Dolomites - Laura Grassi; Maria Luisa Menandro; Federica Obber; Michele Drigo; Matteo Legnardi; Daniela Pasotto; Claudia Maria Tucciarone; Giulia Faustini; Carlo Citterio; Mattia Cecchinato; Giovanni Franzo (Veterinary Research Communications, 2022)